Design and synthesis of efficient heavy-atom-free photosensitizers for photodynamic therapy of cancer - Nguyen, Van Nghia; Park, Sang Jun; Qi, Sujie; Ha, Jeongsun; Heo, Seonye; Yim, Yubin; Baek, Gain; Lim, Chang Su; Lee, Dong Joon; Kim, Hwan Myung; Yoon, Juyoung (Chemical Communications, 2020)
Novel thiocarbonyl derivatives (NIS and CRNS) with excellent ROS generation abilities are synthesized and studied as potential photosensitizers for one- and two-photon excited photodynamic therapy. In particular,NIS-MeandCRNSdisplay outstanding phototoxicity toward HeLa cells under two-photon excitation (800 nm) with negligible dark toxicity.
Keywords: Heavy atoms; HeLa cell; Photo-toxicity; Ros generations; Thiocarbonyl; Two-photon excitations; Two-photon excited; Antineoplastic Agents; Cell Proliferation; Cell Survival; Drug Design; Drug Screening Assays, Antitumor; HeLa Cells; Humans; Molecular Structure; Optical Imaging; Photochemotherapy; Photosensitizing Agents; Sulfhydryl Compounds